PENGEMBANGAN MEDIA PEMBELAJAAN IPA PADA MATERI CAHAYA DAN ALAT OPTIK KELAS VIII MENGGUNAKAN ADOBE FLASH CS.6 - Tari, Tari; Astalini, Astalini; Pathoni, Haerul (EduFisika: Jurnal Pendidikan Fisika, 2019)
This research aims to develop science learning media and know the perception of Shiva. This research wass a research and development study that uses the ADDIE model. The research stages include analysis, design, development, implementation and evaluation. The subject of this research test was grade VIII students SMPN 7 Kota Jambi. The instruments used were media-and material-validation sheet as well as student perception questionnaire. The data were analyzed descriptively. The Media developed has a .swf format in which there are audio, video, animations, images, and comes with questions in each sub-chapter of the material and there was an evaluation of all material. Media and material validation results with an average score of 89 (very good) and 77.5 (good). The results of the student perception analysis gained an average score overall indicator is 80.79 (good). Based on these results, it can be concluded that this science learning media can be used as a self-taught student.